Spatial analysis of the settlement system of Zaporizhia region - Baiteriakov, Oleg; Arsenenko, Iryna; Donchenko, Larisa (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Formulation of the problem. In 2020, there were some radical changes that took place in the administrative and territorial structure of Zaporizhia region; as a result, 5 new administrative districts were created on its territory instead of 20 previous ones, which significantly affected the structure of the regional settlement system. Therefore, the question arises about the study of the settlement system of the region in the new socio-geographical realities. The purpose of the article. The purpose of the article consists in identification of the current state and spatial differences of the system of settlement of the territory of Zaporizhia region after the reform of the administrative and territorial structure. Methods. The study used methods for calculating quantitative and relative indicators of the state of urban and rural settlement systems, the comparative analysis of the assessment results, as well as methods for typing administrative districts according to the structure of the settlement system. Results. For each new district of the region, there were calculated the following indicators: the population density, population concentration index, the average population density of settlements, the average density of settlements, the average distance between them, the leadership index of the administrative centers of the districts, the level of urbanization of the territory by the share of the urban population, according to the hierarchical method of O. Tereshchenko and according to E. Arriaga’s approach. According to these indicators, the spatial differences in the settlement system of the administrative districts of the region were revealed. Differentiation of the system of urban settlements of the administrative districts of the region significantly exceeds the contrast of the average general indicators of the system of settlement of districts. This is especially evident when using hierarchical approaches to determine the level of urbanization. The district systems of rural settlements in Zaporizhia region have smoother differences in terms of similar indicators in comparison with the systems of urban settlement, which indicates the relative rationality of the new administrative-territorial structure. Based on the calculations, a typological grouping of the new administrative districts of Zaporizhia region according to the modern structure of settlement was carried out.As a result of this grouping, 2 types of districts were singled out: 1) districts with a monocentric settlement system; these include Zaporizhia, Melitopol and Berdyansk districts (they are clearly distinguished by the size, functions performed and the impact on the settlement system of multifunctional regional centers); 2) districts with a polycentric dispersed settlement system, these include Vasilievsky and Pologovsky districts (in these districts there are no centers with strongly marked leading positions both in terms of population and functions performed). Scientific novelty and practical significance. For the first time, there was carriedout an assessmentof the settlement system of the new administrative districts of Zaporizhia region; the spatial differencesof the settlement system were revealed according to various indicators. The data obtained can be used to optimize the territorial management of the region, to predict its further development and to work out strategies for socio-economic development.